MODIFICATIONS OF VOWELS IN CONNECTED SPEECH ("Conference on Universal Science Research 2023", 2023)
In connected speech, vowels often undergo modifications or changes to their pronunciation. These modifications occur due to various factors such as coarticulation, assimilation, elision, and reduction. Understanding these modifications is crucial for comprehending natural spoken language. In this article, we will explore some common vowel modifications in connected speech, along with examples.